The Sensitivity Analysis of Whitecapping Dissipation Term for Calibration of SWAN Model Forced with ERA5 Winds in the Gulf of Oman - Amir Siahsarani; Majid Azadi; Behzad Layeghi; Davoud Babazadeh (Nīvār)
Although the accuracy of wind-driven wave height simulation largely depends on the quality of the forced wind field, despite the production of high-quality wind products, the wind fields used for ocean waves modeling are more or less subject to bias. Minimizing the impact of wind errors on wave model output is not a long-term operational solution. A more common method is to calibrate the wave model, which is generally implemented by setting certain coefficients in these models. In the present study, the sensitivity of the simulations of the significant wave height to the terms of the wind input and whitecapping dissipation in a third generation wave model has been investigated. For this purpose, 36 different configurations of the wave model have been used. the results of this study allow us to see the response of the SWAN model as a function of physical parameters. Calibration of the SWAN model using the ERA5 forced wind field significantly improved the simulation accuracy in the Oman Sea. For the Oman Sea, it is recommended to use the expressions of wind input and whitecapping dissipation based on the Janssen formulation with the coefficient C_ds=4.0 in the simulation. Considering the error statistics, the same finding was obtained when the model results were compared with the measurements of the wave recorder buoy of the I.R. of Iran Meteorological Organization (IRIMO) in the northern part of the Oman Sea.